2002
DOI: 10.1002/pits.10032
|View full text |Cite
|
Sign up to set email alerts
|

Negative treatment outcomes of behavioral parent training programs

Abstract: The purposes of this review were to: (a) outline the literature on negative treatment outcomes of behavioral parent training programs, (b) detail variables found to be predictive of negative treatment outcomes, and (c) suggest future directions of study. We suggest that despite scores of studies documenting positive outcomes of behavioral parent training programs, negative treatment outcomes occur for a sizeable minority of families. Existing research has documented a relationship between a number of contextua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(46 citation statements)
references
References 55 publications
1
40
0
5
Order By: Relevance
“…The overall attrition rate from pre-to post-intervention assessment was 22.5% (intervention group 30.9%, control group 13.1%), and from post-to follow-up assessment 20.7%. These attrition rates are within the range of those reported by comparable studies investigating self-directed parenting programs (Assemany & McIntosh, 2002;Markie-Dadds & Sanders, 2006;Montgomery et al, 2009).…”
Section: Allocation and Attritionsupporting
confidence: 61%
“…The overall attrition rate from pre-to post-intervention assessment was 22.5% (intervention group 30.9%, control group 13.1%), and from post-to follow-up assessment 20.7%. These attrition rates are within the range of those reported by comparable studies investigating self-directed parenting programs (Assemany & McIntosh, 2002;Markie-Dadds & Sanders, 2006;Montgomery et al, 2009).…”
Section: Allocation and Attritionsupporting
confidence: 61%
“…Thus, even though the treatment group parents' initial motivation to change likely played a role in establishing the treatment effect, the findings from this study still provide useful information about how this intervention may play out when applied to children who are initially perceived by parents as struggling motivationally. All of the parents completed the two month study, which is striking since reviews of the parent training literature have found that the average reported drop-out rate for parent training is near 30% (Assemany and McIntosh 2002). In a future study, it may be best to utilize wait list controls, so that groups are matched on the perceived need for services.…”
Section: Discussionmentioning
confidence: 98%
“…Several recent reviews have examined the issue of attrition and engagement in child treatment programs, seeking to highlight the importance of the issue and laying the groundwork for additional research (Assemany and McIntosh 2002;Nock and Ferriter 2005;Staudt 2007) This problem is certainly not specific to BPT programs alone, but is generally true of child treatment interventions with studies finding that only one third of families in need of services actually receive them (Leaf et al 1996). Still, only half of those families actually complete treatment (Armbruster and Kazdin 1994;Harpaz-Rotem et al 2004;Kazdin and Mazurick 1994).…”
Section: Introductionmentioning
confidence: 96%